2012
DOI: 10.2105/ajph.2011.300638
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating Safety and Sexual Risk Reduction With Clients in Unsanctioned Safer Indoor Sex Work Environments: A Qualitative Study

Abstract: Objectives To examine how unique, low-barrier housing programs for women that are functioning as unsanctioned quasi-brothels under special needs housing regulations in a Canadian urban setting influence risk negotiation with clients in sex work transactions. Methods We conducted 39 semi-structured qualitative interviews and 6 focus groups with women who live in low-barrier, supportive housing for marginalized sex workers with substance use issues. All interviews were transcribed verbatim and thematically ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
142
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 137 publications
(151 citation statements)
references
References 22 publications
(28 reference statements)
7
142
1
1
Order By: Relevance
“…Although sex workers were no longer being targeted directly by the police, the enforcement environment that continued to target clients during our study period appeared to put pressure on sex workers to rush the screening. Initial screening of prospective clients, such as checking bad date sheets, and negotiating the terms of the transaction, such as where it will take place, the fee, and condom use, is essential to protect the safety of sex workers [7,11,13,[23][24][25], and among the key evidence cited by the Supreme Court of Canada in striking down the old criminal laws. When negotiations are rushed or forgone, sex workers are known to face significantly increased risk of violence, abuse, and condom refusal, which can result in HIV/STIs [7,11,13,[23][24][25]34].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although sex workers were no longer being targeted directly by the police, the enforcement environment that continued to target clients during our study period appeared to put pressure on sex workers to rush the screening. Initial screening of prospective clients, such as checking bad date sheets, and negotiating the terms of the transaction, such as where it will take place, the fee, and condom use, is essential to protect the safety of sex workers [7,11,13,[23][24][25], and among the key evidence cited by the Supreme Court of Canada in striking down the old criminal laws. When negotiations are rushed or forgone, sex workers are known to face significantly increased risk of violence, abuse, and condom refusal, which can result in HIV/STIs [7,11,13,[23][24][25]34].…”
Section: Resultsmentioning
confidence: 99%
“…For example, sex workers experienced pressure from potential clients to quickly negotiate terms of the sexual transactions. This served to impede sex worker's ability to screen clients for potential weapons or intoxication and check 'bad date' sheets for past violent clients, which are well documented techniques for sex workers to reduce harms such as risk of violence, abuse and HIV/STIs [7,11,13,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Although timely access to health care remains a priority in Canada, studies indicate that Canadians are less likely than citizens of other countries to have same-day access to health care services, and that the wait for these services can take, on average, six days before they are to see their health care providerwhich leaves many Canadians resorting to hospital emergency departments for their primary health care (Schoen et al , 2007). Numerous studies indicate that, if you are a marginalized woman in Canada, your access to health care is compromised ten-fold (Bloch, Razmotits, & Giambrone, 2011;Browne et al, 2012;Goodman, 2006;Krusi et al , 2012;Kurtz, Nyberg, Van Den Tillaart, & Mills, 2008;Lazarus et al , 2012;Loppie & Wien, 2009;Salmon, Livingston, Browne, & Pederson, 2009;Tappet al, 2011).…”
Section: Accessmentioning
confidence: 99%
“…In 1996, when three homeless men froze to death in Toronto, hostels were organized to house the homeless during poor weather conditions (Hardill, 2006). Other outreach centers across Canada provide access for marginalized populations to obtain harm reduction supplies, which essentially include clean needles, condoms, food, water, and telephone access (Krusi et al, 2012 Vancouver in 2003, has resulted in a decrease in the incidents of overdoses and the transmission of blood-borne diseases, and, an increase the retention rates for people in detox and treatment facilities, along with an increase in the exposure of the marginalized population to the health care system (Small, 2012). It has also been shown that the InSite program has resulted in a reduction in injections taking place in public places, has kept dirty needles off the streets, and has reduced the use of emergency services, while increasing access to health care providers (namely nurses) and other resources, and generally keeping people alive (Jozaghi & Andresen, 2013).…”
Section: Outreach Servicesmentioning
confidence: 99%
See 1 more Smart Citation